Language and Human Understanding: The Roots of Creativity in Speech and Thought - David Braine (Catholic University of America Press, 2014)
A right account of language is, I believe, the key to a right account of the nature of human understanding and thought, and thereby the key to a right understanding of human nature as a whole. Yet the whole theory of language is in considerable disorder, and my aim must therefore be first to seek to remedy this. This will take me into the heart of current debates in linguistics, philosophy, and psychology, and lead me to undertake an extended study of grammar. The effect will be to show how language exhibits the ultimate freedom of the human intellect and will from conformity with mechanically applicable rules and from limitations set by neurology. The brain plays a key role in the normal functioning of the human mind, but does not determine or shape linguistic understanding and thinking in the medium of words, as this develops through adaptation to and learning within a social external environment of other speakers and hearers, all within a setting of natural things. Such understanding and thinking have to be considered the activities not of brains or minds, but of human beings as such. In effect the animal becomes intellectual in nature as soon as the brain reaches such malleability in its modes of functioning as to set no restrictions on the animal or person’s intellectual operation, allowing autonomy to the mind’s operation.